163k views
0 votes
Differentiate with respect to x

Differentiate with respect to x-example-1
User Ryanve
by
5.0k points

2 Answers

4 votes


\bf y = \cfrac{6x^2-9x^4}{3x}\implies \cfrac{dy}{dx}=\stackrel{\textit{quotient rule}}{\cfrac{(12x-36x^3)(3x)-(6x^2-9x^4)3}{(3x)^2}} \\\\\\ \cfrac{dy}{dx}=\cfrac{(36x^2-108x^4)~~~~-~~~~(18x^2-27x^4)}{(3x)^2} \\\\\\ \cfrac{dy}{dx}=\cfrac{36x^2-108x^4~~~~-18x^2+27x^4}{(3x)^2}\implies \cfrac{dy}{dx}=\cfrac{18x^2-81x^4}{9x^2}


\bf \cfrac{dy}{dx}=\cfrac{~~\begin{matrix} 9x^2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~(2-9x^2)}{~~\begin{matrix} 9x^2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies \cfrac{dy}{dx}=2-9x^2

User Moropus
by
5.4k points
4 votes
The answer is 2x - 3x^3. You have to divide the coefficients and subtract the exponents.
User Soupybionics
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.